Induksi Ekstrak Pegagan Secara in vitro terhadap Proliferasi dan Diferensiasi Sel-Sel Otak Besar Anak Tikus (IN VITRO INDUCTION OF CENTELLA ASIATICA (PEGAGAN) EXTRACT ON THE PROLIFERATION AND DIFFERENTIATION OF NEWBORN RAT CORTEX CEREBRI CELLS) - Djuwita, Ita; Rahminiwati, Min; Darusman, Latifah Kosim; Sa’diah, Siti (Jurnal Veteriner, 2013)
The aim of the study was to analyze the potency of Centella asiatica extract to induce proliferation andneurogenesis process of newborn rats cortex cerebri.   Research has been conducted on in vitro culture ofthree days old rat (Sprague Dawley) cerebrum cells in DMEM (Dulbecco’s Modiûed Eagle’s Medium)containing 10% NEAA (Non Essential Amino Acid), 1 mM NaHCO3, 10% NBCS (Newborn Calf Serum)and 50 µg/mL gentamycin (mDMEM), with and without Centella asiatica (CA) leaf extracts. The experimentwas set in five groups of treatment consisted of positive control (mDMEM+30 µg/mL asiaticoside (AC)),negative control (mDMEM), and mDMEM with three concentration of CA extract i.e. 100 ppm, 200 ppmand 400 ppm. Culture was done in 5% CO2 incubator at 37oC for six days. The parameters observed werecells proliferation based on Population Doubling Time (PDT), neuron and glia composition, and the lengthof axon and dendrite. Cells concentration were counted using Newbauer hemocytometer.  Neuron and gliacells were determined based on morphology after Hematoxylin-Eosin staining, and the length of axon anddendrite were measured using eyepiece micrometer. Data were analyzed using ANOVA and Duncan test.The results showed that Centella asiatica extract at concentration 100 ppm could induce neurogenesisand increased the axon length growth.  However, at concentration 200 and 400 ppm, CA extract  inhibitedthe neuronal cells proliferation and the axonal growth (P<0,05). In conclusion, induction of Centella asiaticaextracts at concentration of 100 ppm on the cortex cell cerebrum cells culture increase the axon lengthgrowth and tends to induce neurogenesis; however at higher concentration CA extract was neurotoxic.
Keywords: cell culture, neuron, Centella asiatica leaf extracts, neurogenesis